Efficacy and Limitations of rCBF-SPECT in the Diagnosis of Alzheimer's Disease With Amyloid-PET. Issue 5 (August 2019) - Takahashi, Miwako; Tada, Tomoko; Nakamura, Tomomi; Koyama, Keitaro; Momose, Toshimitsu
This study aimed to assess efficacy and limitations of regional cerebral blood flow imaging using single-photon emission computed tomography (rCBF-SPECT) in the diagnosis of Alzheimer's disease (AD) with amyloid-positron emission tomography (amyloid-PET). Thirteen patients, who underwent both rCBF-SPECT and amyloid-PET after clinical diagnosis of AD or mild cognitive impairment, were retrospectively identified. The rCBF-SPECTs were classified into 4 grades, from typical AD pattern to no AD pattern of hypoperfusion; amyloid-beta (Aβ) positivity was assessed by amyloid-PET. Four patients were categorized into a typical AD pattern on rCBF-SPECT, and all were Aβ+. The other 9 patients did not exhibit a typical AD pattern; however, 4 were Aβ+. The Mini-Mental State Examination score and Clinical Dementia Rating scale were not significantly different between Aβ+ and Aβ– patients. A typical AD pattern on rCBF-SPECT can reflect Aβ+; however, if not, rCBF-SPECT has a limitation to predict amyloid pathology.